Pengaruh Penyuluhan terhadap Kepatuhan dalam Melakukan Imunisasi TT pada Calon Pengantin di Wilayah Kerja Puskesmas Klakah - Rika Rahma Yulianingrum; Tutik Ekasari; Homsiatur Rohmatin (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
The bride and groom who are about to get married have to prepare a lot of things. Where bridegroom will carry out a complete medical test. The research design used was One Group Pretest-Posttest (Initial Test-Final Test in a single group). Sampling was taken using Total Sampling technique. The research data used the t-test for bivariate analysis using the Wilcoxon Signed Test. The results of the study were obtained from 80 respondents to the compliance of the prospective bride and groom in carrying out TT immunization before being given counseling, 16 people (20 percent) of prospective brides were obedient and 64 people (80 percent) of prospective brides were not obedient. Meanwhile, the obedience of the bride and groom in carrying out TT immunization after being given counseling was obtained by 55 people (68.8 percent) of the prospective bride and groom who were obedient and 25 people (31.3 percent) of the bride and groom who did not comply. The effectiveness test was carried out using the Wilcoxon test, and a significance value (p) of 0.000 was obtained. Which means that there is a significant effect of counseling on the level of compliance of the bride and groom in carrying out TT immunization.